2016
DOI: 10.7754/clin.lab.2015.151203
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Status and DNA Damage Following Analgesic Treatment in Patients with Acute Pancreatitis

Abstract: There is no difference between the effects of paracetamol, dexketoprofen, and tramadol, which are commonly used to manage acute pain in AP, on DNA damage in human T-lymphocytes and on serine parameters of oxidative status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…moderate to strong traumatic musculoskeletal pain (Pagliara et al, ). Tramadol is an effective agent in the management of pain in acute pancreatitis, however, no significant difference in efficacy was found between NSAIDs (paracetamol, dexketoprofen) and tramadol in terms of pain control, (Gülen et al, ) oxidative stress and DNA damage parameters in AP settings (Gulen et al, ). Opioids are reported to decrease the need of supplementary analgesia ( n = 162, 3 studies) in acute pancreatitis highlighting their efficacy (Basurto Ona et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…moderate to strong traumatic musculoskeletal pain (Pagliara et al, ). Tramadol is an effective agent in the management of pain in acute pancreatitis, however, no significant difference in efficacy was found between NSAIDs (paracetamol, dexketoprofen) and tramadol in terms of pain control, (Gülen et al, ) oxidative stress and DNA damage parameters in AP settings (Gulen et al, ). Opioids are reported to decrease the need of supplementary analgesia ( n = 162, 3 studies) in acute pancreatitis highlighting their efficacy (Basurto Ona et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a statistically significant increase was observed in the DNA DI of patients with D CML relative to the control group. The causes of DNA damage are multifactorial, and oxidative damage to this molecule has been attributed to drug therapy in other diseases [Gulen et al, 2016;Chen et al, 2017].…”
Section: Dear Editormentioning
confidence: 99%